Short-Term Changes in Mental, Physical, and Social Factors After Metabolic Bariatric Surgery in Adolescents: A Nationwide Prospective Cohort Study - Goldenshluger, Ariela; Maor, Tamar; Via-Kagan, Renana; Zelekha, Orly; Gepner, Yftach (Frontiers in Nutrition, 2022)
Background: Metabolic bariatric surgery (MBS) is an effective treatment for adolescents with severe obesity. However, changes in mental, physical and social factors, and their association with the extent of excess weight loss (%EWL) after MBS, remain controversial. Methods: We followed 97 adolescents (64% females, aged 17.0±0.9 years, BMI 46.1±5.9 kg/m2) before and nine months following MBS in a multi-center, prospective cohort study. Changes in mental, physical and social factors were assessed by self-reported questionnaires and associations with %EWL were evaluated after adjustment for potential confounders. Results: BMI decreased by 30%, and all physical parameters significantly improved (p≤0.001). Energy level increased by 24%, mood level by 14%, and mental health by 9.5% (p≤0.002). Social parameters were also improved, with a significant decrease in social rejection (p=0.02), and an increase in participation in after-school social activities (p=0.008). Mental health improvement was associated with baseline social rejection (r=0.514, p<0.001). The improvement in all factors was not related to the extent of %EWL. Conclusions: MBS in adolescents led to a meaningful decrease in BMI and a notable improvement in physical, mental, and social factors that were not related to %EWL. Patients experiencing social rejection may experience greatly improved mental health following BS.